Modulation of iron transport proteins in human colorectal carcinogenesis. Issue 10 (26th April 2006) - Brookes, M J; Hughes, S; Turner, F E; Reynolds, G; Sharma, N; Ismail, T; Berx, G; McKie, A T; Hotchin, N; Anderson, G J; Iqbal, T; Tselepis, C
Abstract : Background and aims: Total body iron and high dietary iron intake are risk factors for colorectal cancer. To date there is no comprehensive characterisation of iron transport proteins in progression to colorectal carcinoma. In this study, we examined expression of iron import (duodenal cytochrome b (DCYTB), divalent metal transporter 1 (DMT1), and transferrin receptor 1 (TfR1)) and export (hephaestin (HEPH) and ferroportin (FPN)) proteins in colorectal carcinoma. Methods: Perl's staining was used to examine colonocyte iron content. Real time polymerase chain reaction (PCR) and western blotting were used to examine mRNA and protein levels of the molecules of interest in 11 human colorectal cancers. Semiquantitative immunohistochemistry was used to verify protein levels and information on cellular localisation. The effect of iron loading on E-cadherin expression in SW480 and Caco-2 cell lines was examined by promoter assays, real time PCR and western blotting. Results: Perl's staining showed increased iron in colorectal cancers, and there was a corresponding overexpression of components of the intracellular iron import machinery (DCYTB, DMT1, and TfR1). The iron exporter FPN was also overexpressed, but its intracellular location, combined with reduced HEPH levels, suggests reduced iron efflux in the majority of colorectal cancers examined. Loss of HEPH and FPN expression was associated with more advanced disease. Iron loading Caco-2 and SW480 cells caused cellular proliferation and E-cadherin repression. Conclusions: Progression to colorectal cancer is associated with increased expression in iron import proteins and a block in iron export due to decreased expression and aberrant localisation of HEPH and FPN, respectively. This results in increased intracellular iron which may induce proliferation and repress cell adhesion.